A new damsel-dragonfly (Odonata: Anisozygoptera: Campterophlebiidae) from the earliest Jurassic of the Junggar Basin, northwestern China. Issue 4 (2nd October 2019) - Zheng, Daran; Wang, He; Nel, AndrÉ; Dou, Longhui; Dai, Zhenlong; Wang, Bo; Zhang, Haichun
Abstract : Zheng, D., Wang, H., Nel, A., Dou, L., Dai, Z., Wang, B. & Zhang, H. 27 June 2019. A new damsel-dragonfly (Odonata: Anisozygoptera: Campterophlebiidae) from the earliest Jurassic of the Junggar Basin, northwestern China. Alcheringa XX, X–X. ISSN 0311-5518. A new genus and species of campterophlebiid damsel-dragonfly, Jurassophlebia xinjiangensis gen. et sp. nov., is described from the Lower Jurassic Badaowan Formation in the Junggar Basin, northwestern China. Jurassophlebia differs from all other campterophlebiid genera in having PsA in the same orientation as the distal branch of AA, and in its uniquely open subdiscoidal cell with very acute apical angle in the hind wing. The new discovery adds to the Asian diversity of damsel-dragonflies in the earliest Jurassic. Daran Zheng* [dranzheng@gmail.com ], He Wang [hwang@nigpas.ac.cn ], Bo Wang [bowang@nigpas.ac.cn ], and Haichun Zhang [hczhang@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, PR China; André Nel [anel@mnhn.fr ], Institut de Systématique, Évolution, Biodiversité, ISYEB-UMR 7205-CNRS, MNHN, UPMC, EPHE, Muséum national d'Histoire naturelle, Sorbonne Universités, 57 rue Cuvier, CP 50, Entomologie, F-75005, Paris, France; Longhui Dou [345317122@qq.com ], Comprehensive Geology Exploration Team, Xinjiang Coalfield Geology Bureau, West Mountain Road, Ürümqi 830000, PR China; Zhenlong Dai [286321388@qq.com ], No.9 Geological Team, Xinjiang Bureau of Geology and Mineral Resources, Ürümqi 830011, PR China; Daran Zheng also affiliated with Department of Earth Sciences, The University of Hong Kong, Hong Kong Special Administrative Region, PR China.